2021
DOI: 10.1088/1755-1315/739/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Integration of conservation and economic development in Gunung Leuser National Park

Abstract: Sumatran Elephant has economic benefits as an ecotourism attraction. The most appropriate tourism management is making the tour package attractive, safe, and sustainable. The increasing number of visitors to natural destinations has a significant impact. Feasibility studies can be used to consider making a decision, either rejecting, accepting, retaining, and stopping the effort. Therefore, a financial feasibility analysis is required to see the feasibility of using Sumatran elephants as an ecotourism package.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Regarding the potential of the Sipinsur area, Damanik et al (2021) also reported the same thing. According to Purwoko et al (2020), the impact of tourism on the economy can be both positive and negative. Ecotourism in many conservation areas tends to be an alternative conservation approach to improve livelihoods.…”
Section: Results and Discussion 1 Ecotourism Potential In Tourist Are...mentioning
confidence: 99%
“…Regarding the potential of the Sipinsur area, Damanik et al (2021) also reported the same thing. According to Purwoko et al (2020), the impact of tourism on the economy can be both positive and negative. Ecotourism in many conservation areas tends to be an alternative conservation approach to improve livelihoods.…”
Section: Results and Discussion 1 Ecotourism Potential In Tourist Are...mentioning
confidence: 99%
“…Whenever possible, what kind of economic development and the cultivation of talents are the top priorities of a country []- [2]. In today's world, the new technological revolution characterized by information technology is on the rise, and the information technology revolution has brought unprecedented opportunities for the development of various industries []- [4].…”
Section: Introductionmentioning
confidence: 99%